Latin American Beer Production and Import Demand for Regional Malt and Malted Barley - García Arancibia, Rodrigo (2024)
Over the last 25 years, the Latin American beer sector has undergone important changes. The growth in beer production, consumption, and trade has been accompanied by a greater demand for malt and barley produced and traded in the region, displacing other traditional export countries of these inputs. Based on these facts, we studied the long-term relationship between this increase in beer production and the prices of imported inputs. In addition, we estimated the elasticities of demand of imported inputs of the main Latin American brewing countries. This allows us to infer about Latin America´s competitive position as a supplier of its own beer inputs.